The effects of combined glucose-electrolyte and sodium bicarbonate ingestion on prolonged intermittent exercise performance - Price, M. J.; Cripps, D. (Journal of Sports Sciences, 2012)
This study examined the effects of combined glucose and sodium bicarbonate ingestion prior to intermittent exercise. Ninemales (mean ± s age 25.4 ± 6.6 years, body mass 78.8 ± 12.0 kg, maximal oxygen uptake ([Vdot]O2max) 47.0 ± 7ml/kg·min) undertook 4 × 45 min intermittent cycling trials including 15 × 10 s sprints one hour after ingesting placebo (PLA), glucose (CHO), sodium bicarbonate (NaHCO3) or a combined CHO and NaHCO3 solution (COMB). Post ingestion blood pH (7.45 ± 0.03, 7.46 ± 0.03, 7.32 ± 0.05, 7.32 ± 0.01) and bicarbonate (30.3 ± 2.1, 30.7 ± 1.8, 24.2 ± 1.2, 24.0 ± 1.8 mmol/l) were greater for NaHCO3 and COMB when compared to PLA andCHO, remaining elevated throughout exercise (main effect for trial; P < 0.05). Blood lactate concentration was greatest throughout exercise for NaHCO3 and COMB (main effect for trial; P < 0.05). Blood glucose concentration was greatest 15 min post-ingestion for CHO followed by COMB, NaHCO3 and PLA (7.13 ± 0.60, 5.58 ± 0.75, 4.51 ± 0.56, 4.46 ± 0.59 mmol/l, respectively; P < 0.05). Gastrointestinal distress was lower during COMB compared to NaHCO3 at 15 min post-ingestion (P < 0.05). No differences were observed for sprint performance between trials (P = 1.00). The results of this study suggest that a combined CHO and NaHCO3 beverage reduced gastrointestinal distress and CHO availability but did not improve performance. Although there was no effect on performance an investigation of the effects in more highly trained individuals may be warranted.